2007
DOI: 10.1021/bi602389p
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Activation of Ras Proteins by Electrophilic Prostanoids with Different Structure are Site-Selective

Abstract: Cyclopentenone prostanoids (cyP) arise as important modulators of inflammation and cell proliferation. Although their physiological significance has not been fully elucidated, their potent biological effects have spurred their study as leads for the development of therapeutic agents. A key determinant of cyP action is their ability to bind to thiol groups in proteins or in glutathione through Michael addition. Even though several protein targets for cyP addition have been identified, little is known about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 49 publications
7
76
1
Order By: Relevance
“…The similarity of structure in these two molecules suggested that they might have similar interactions with cell proteins. Previous studies have shown similar effects of 15dPGJ 2 to OxPAPC in several pathways ( 7,9,12,14,15,(22)(23)(24)(25)(26)(27). We now demonstrate that OxPNB and 15dPGJ 2 bind to the same cysteines in H-Ras (C181 and C184) and that 15dPGJ 2 can inhibit the binding of OxPNB to H-Ras.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The similarity of structure in these two molecules suggested that they might have similar interactions with cell proteins. Previous studies have shown similar effects of 15dPGJ 2 to OxPAPC in several pathways ( 7,9,12,14,15,(22)(23)(24)(25)(26)(27). We now demonstrate that OxPNB and 15dPGJ 2 bind to the same cysteines in H-Ras (C181 and C184) and that 15dPGJ 2 can inhibit the binding of OxPNB to H-Ras.…”
Section: Discussionsupporting
confidence: 75%
“…study of the role played by specifi c cysteines in Ras activation (12)(13)(14)(15). The current study examines the mechanism by which OxPNB interacts with H-Ras.…”
mentioning
confidence: 99%
“…This property is essential for cyPG biological actions (4), including PPAR activation (5) and inhibition of NF-kB and AP-1 transcription factors (1,6). A-and J-series cyPG were initially observed to share several protein targets and biological actions (7)(8)(9). However, recent studies have shown that cyPG with different structures may target selective subsets of cellular proteins (10), and even different residues within the same protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that cyPG with different structures may target selective subsets of cellular proteins (10), and even different residues within the same protein. Ras proteins and histone deacetylases constitute examples of this intra-and intermolecular selectivity (9,11). Identification of the factors involved in the selectivity of protein modification by different cyPG, as well as of the selectively modified targets, could unveil potential opportunities for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling molecules such as nitric oxide (NO) or the cyclopentenone prostaglandins (CyPG) PGA 1 and 15d-PGJ 2 have been reported to trigger cellular Ras activation in a process including direct modification of specific cysteine residues of the C-terminal Ras region. [96][97][98][99] In the current paradigm, upon RTK or GPCR activation, Sos proteins are recruited to the plasma membrane via formation of a complex with Grb2 adaptor proteins. 5,[57][58][59] However, a still unanswered question is the mechanism of the possible participation of Sos in the process of CyPG-mediated Ras activation.…”
Section: Monographsmentioning
confidence: 99%